Analisis Keterampilan Komunikasi Peserta Didik Kelas V pada Model Pembelajaran Inkuiri dan Radec - Suryadi, Tatang; Sopandi, Wahyu; Sujana, Atep (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Communication skills are one of the fundamental skills that all students must have. The role of the teacher is very influential on students' communication skills. One thing that can support the development of their communication skills is the learning model implemented by the teacher. Therefore, it is very important to use the right learning model to train students' communication skills. The aim of this research is to provide an overview of students' communication skills by applying the inquiry and RADEC learning models to material about the properties of light. The method in this research uses a descriptive qualitative approach with the research subjects involving fifth grade students from one of the state elementary schools in Bandung City. Observation, interviews and documentation were used as data collection techniques. The data analysis technique in this research uses the Miles and Huberman model, namely, data collection, data reduction, data presentation, and drawing conclusions or verification. Data validity was tested through a triangulation approach. The research results stated that the percentage of students' communication skills using the inquiry learning model reached 77.12%, while the percentage of students' communication skills using the RADEC learning model reached 80.34%. It can be concluded that the RADEC learning model has a more effective impact in training students' communication skills compared to the Inquiry learning model. However, both learning models still provide opportunities for students to participate actively and practice their communication skills.